Alloy material, method for producing the same, electrical contact material, and switching device
Patent Information
- Application Number
- CN202611353104.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]然而,传统CuCr40材料在多次开断大电流时,仍面临电弧集中烧蚀、表面形成大熔坑和液滴喷溅等问题,导致电接触性能下降和使用寿命缩短
[0026]本申请通过在铜铬合金中微量添加镍、铁或铋元素,利用增强金属与铬、铜的协同作用细化并均匀化微观组织,使合金材料的硬度得到显著提升,耐电压强度、抗电弧侵蚀性能得到改善,截流值降低,从而适用于开关设备。
Smart Images

Figure CN122959567A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of alloy materials technology, and in particular to an alloy material and its preparation method, an electrical contact material, and a switching device. Background Technology
[0002] CuCr alloys are widely used as electrical contact materials in high-voltage switchgear such as medium- and high-voltage vacuum circuit breakers and contactors due to their excellent electrical conductivity, resistance to arc erosion, and resistance to welding. Among them, CuCr40 alloy with a Cr content of approximately 40 wt% has become one of the most widely used composition systems due to its good balance between electrical conductivity and resistance to arc erosion. With the development of power systems towards higher voltage and larger capacity, the requirements for the comprehensive performance of contact materials are constantly increasing, and CuCr40 alloy has broad application prospects under harsh operating conditions.
[0003] However, traditional CuCr40 materials still face problems such as concentrated arc erosion, large molten pits on the surface, and droplet splashing when repeatedly interrupting high currents, leading to decreased electrical contact performance and shortened service life. To solve these problems, existing technologies attempt to modify CuCr alloys by adding a third component, such as elements like Mo, W, and Zr, or ceramic particles like Al2O3 and Y2O3. However, these methods or processes are complex, or lead to a significant decrease in the material's plasticity and toughness, or insufficient stability at high arc temperatures, making it difficult to simultaneously meet the comprehensive requirements of high hardness, high conductivity, high withstand voltage, and low current cutoff value. Summary of the Invention
[0004] Therefore, this application provides an alloy material with high hardness, high conductivity, high pressure resistance and low current cut-off value, a method for preparing the same, an electrical contact material and a switching device.
[0005] This application provides an alloy material comprising, by mass percentage, 59% to 61% copper, 32% to 38% chromium, and 1% to 7.5% reinforcing metal, wherein the reinforcing metal comprises one or more of nickel, iron, and bismuth.
[0006] In one embodiment, the sum of the mass percentages of the reinforcing metal and chromium is 39% to 41% of the alloy material.
[0007] In one embodiment, the average grain size of the alloy material is 10 μm to 50 μm.
[0008] This application also provides a method for preparing an alloy material, comprising the following steps:
[0009] Prepare elemental copper, elemental chromium, and reinforcing elemental metals according to the composition of the above alloy materials;
[0010] The mixture of the copper, chromium and reinforcing metals is then ground, annealed and subjected to spark plasma sintering.
[0011] In one embodiment, the grinding conditions satisfy one or more of the following conditions:
[0012] (1) Rotation speed is 850 r / min~950 r / min;
[0013] (2) The grinding media includes anhydrous ethanol;
[0014] (3) The ball-to-material ratio is (14~16):1;
[0015] (4) The grinding time is 10 to 15 hours.
[0016] In one embodiment, the annealing conditions satisfy one or both of the following conditions:
[0017] (1) The annealing temperature is 600℃~700℃;
[0018] (2) The annealing time is 1 to 3 hours.
[0019] In one embodiment, the conditions for spark plasma sintering satisfy one or more of the following conditions:
[0020] (1) The sintering temperature is 950℃~1050℃;
[0021] (2) The sintering pressure is 30 MPa~50 MPa;
[0022] (3) The heat preservation time is 5 to 15 minutes;
[0023] (4) The discharge plasma sintering is performed using a pulsed DC current with a 12:2 on / off pulse mode.
[0024] This application also provides an electrical contact material, including the alloy material described above.
[0025] This application also provides a switching device, including the electrical contact material as described above.
[0026] This application refines and homogenizes the microstructure by adding trace amounts of nickel, iron, or bismuth to a copper-chromium alloy, utilizing the synergistic effect of the reinforcing metal with chromium and copper. This significantly improves the hardness of the alloy material, enhances its voltage resistance and arc erosion resistance, and reduces its current-cutting value, making it suitable for switchgear. Attached Figure Description
[0027] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein:
[0028] Figure 1 The images show SEM images and particle size distribution diagrams of the alloy materials in Examples 1, 2, and Comparative Example 1 of this application.
[0029] Figure 2 The images provided are SEM images and EDS results of the alloy materials in Examples 1, 2, and Comparative Example 1 of this application. Detailed Implementation
[0030] To facilitate understanding of this application, it may be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0032] As used herein, the term "and / or" encompasses any one of two or more of the related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" includes three parallel options: A, B, and "a combination of A and B".
[0033] In this document, unless otherwise stated, "one or more" means any one of the listed items or any combination of the listed items. Similarly, "one or more" and other instances of "one or more" are to be understood in the same way unless otherwise stated.
[0034] In this document, terms such as "further," "even further," "especially," "for example," "like," "example," and "exemplary" are used for descriptive purposes to indicate a connection in the coverage of different technical solutions presented earlier and later. However, they should not be construed as limitations on the preceding technical solution or on the scope of protection of this document. Unless otherwise specified, in this document, A (e.g., B) indicates that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0035] In this document, "optionally," "optionally," and "optional" mean that something is optional, that is, it is selected from either "present" or "absent." If multiple "options" appear in a technical solution, unless otherwise specified and there are no contradictions or mutual constraints, each "option" is independent. In this application, descriptions such as "optionally contains" and "optionally includes" indicate "contains or does not contain." "Optional component X" indicates whether component X exists or does not exist, or whether component X is contained or not.
[0036] In this document, the terms "first aspect," "second aspect," "third aspect," and "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," and "fourth" serve only as a non-exhaustive enumeration and should be understood as not constituting a closed limitation on quantity.
[0037] In this article, the technical features described in an open-ended manner include both closed technical solutions composed of the listed features and open technical solutions that include the listed features.
[0038] In this document, when referring to numerical intervals (i.e., numerical ranges), unless otherwise specified, the distribution of selectable values within a numerical interval is considered continuous, and includes the two endpoints (i.e., the minimum and maximum values) of the numerical interval, as well as every value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all subranges included therein. The "numerical value" in this numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, and other numerical interval types.
[0039] The present application will be further described in detail below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application. For experimental methods in the following embodiments where specific conditions are not specified, please refer to the guidelines given in this application, or follow experimental manuals or conventional conditions in the art, or follow the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0040] In the specific embodiments described below, the measurement parameters of the raw material components may have slight deviations within the weighing accuracy range unless otherwise specified. For temperature and time parameters, acceptable deviations due to instrument testing accuracy or operational precision are permissible. "Ambient temperature" refers to 25°C; "atmospheric pressure" refers to 100 kPa or 101 kPa.
[0041] This application provides an alloy material comprising, by mass percentage, 59% to 61% copper, 32% to 38% chromium, and 1% to 7.5% reinforcing metal, wherein the reinforcing metal includes one or more of nickel, iron, and bismuth, and the sum of the mass percentages of copper, chromium, and reinforcing metal is 100%.
[0042] This application refines and homogenizes the microstructure by adding trace amounts of nickel, iron, or bismuth to a copper-chromium alloy, utilizing the synergistic effect of the reinforcing metal with chromium and copper. This significantly improves the hardness of the alloy material, enhances its voltage resistance and arc erosion resistance, and reduces its current-carrying capacity, making it suitable for switchgear.
[0043] In this application, copper, as the matrix material, provides excellent electrical and thermal conductivity; chromium, as the main alloying element, forms a two-phase structure with copper that is insoluble in each other, providing high hardness and resistance to arc erosion; the reinforcing metal is used to further regulate the microstructure and interface properties, and comprehensively improves the material performance by refining the grains and improving the interfacial bonding strength.
[0044] Furthermore, the sum of the mass percentages of chromium and reinforcing metals is 39% to 41% for alloy materials.
[0045] Specifically, the chromium content is 32% to 38%, but can be, but is not limited to, 32%, 33%, 35%, 37%, and 38%. Chromium in this range can form a continuous Cr phase network, effectively resisting arc erosion; if the chromium content is too low, the Cr phase will be discontinuous, and the arc resistance will decrease; if the chromium content is too high, the material will become more brittle and the processing performance will deteriorate.
[0046] Specifically, the content of reinforcing metal is 1% to 7.5%, and can be, but is not limited to, 1%, 2%, 3%, 5%, 7%, and 7.5%. The addition of trace amounts of reinforcing metal can refine the grains and improve the bonding strength of the Cu-Cr interface; if the addition amount is too low, the effect will be insignificant; if the addition amount is too high, it will lead to the aggregation of the second phase, which will reduce the material properties.
[0047] Specifically, when the reinforcing metal is nickel, its content is 1% to 3%, and can be, but is not limited to, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.5%, or 3%. Nickel has good compatibility with chromium and copper, which can effectively refine the grains and improve hardness while maintaining good electrical conductivity.
[0048] Specifically, when the reinforcing metal is iron, its content is 1% to 3%, and can be, but is not limited to, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.5%, or 3%. The addition of iron can significantly improve the hardness of the material and at the same time improve its compressive strength.
[0049] Specifically, when the reinforcing metal is a mixture of iron and nickel, the total mass percentage of iron and nickel is 1% to 3%, which can be, but is not limited to, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.5%, or 3%, and the mass ratio of iron to nickel is, for example, 1:1. Nickel has good compatibility with chromium and copper, which can improve the Cu-Cr phase interface bonding and promote the uniform distribution of the chromium phase; iron can significantly refine the powder and chromium phase structure through solid solution strengthening; when the two are added together, they synergistically play a role in interface regulation and grain refinement strengthening, avoiding the agglomeration of reinforcing metal, making the chromium phase distribution more uniform, thereby improving hardness while taking into account voltage resistance and reducing current cutoff value, resulting in a smooth arc ablation surface without obvious cracks and droplet splashing.
[0050] Specifically, when the reinforcing metal is bismuth, its content is 2.5% to 7.5%, and can be, but is not limited to, 2.5%, 3%, 5%, 7%, and 7.5%. The addition of bismuth can effectively improve compressive strength, but too high a content will lead to a decrease in hardness, so it needs to be controlled within this range.
[0051] Specifically, the average grain size of the alloy material is 10μm to 50μm, but can be, but is not limited to, 10μm, 20μm, 30μm, 40μm, and 50μm. Fine grains can increase the phase interface area, thereby improving the overall mechanical properties and resistance to arc erosion of the material.
[0052] This application also provides a method for preparing an alloy material, comprising the following steps:
[0053] Prepare elemental copper, elemental chromium, and reinforcing elemental metals according to the composition of the above alloy materials;
[0054] The mixture of elemental copper, elemental chromium, and reinforcing elemental metals is then ground, annealed, and subjected to spark plasma sintering.
[0055] Specifically, the grinding conditions meet one or more of the following conditions: the rotation speed is 850 r / min to 950 r / min, which may include, but is not limited to, 850 r / min, 880 r / min, 900 r / min, 920 r / min, and 950 r / min; the grinding media includes anhydrous ethanol; the ball-to-material ratio is (14~16):1, which may include, but is not limited to, 14:1, 14.5:1, 15:1, 15.5:1, and 16:1. The ball milling time is 10 hours to 15 hours, which may include, but is not limited to, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, or 15 hours. This rotation speed, grinding time, and ball-to-material ratio can achieve sufficient mixing and mechanical alloying of the various metal elements. If the rotation speed is too low, the mixing will be uneven; if it is too high, it will lead to overwork hardening. If the ball-to-material ratio is too low, the grinding efficiency will be low; if it is too high, the energy consumption will increase.
[0056] Specifically, the annealing conditions should meet one or two of the following conditions: the annealing temperature is 600℃~700℃, which may include, but is not limited to, 600℃, 620℃, 650℃, 680℃, and 700℃; the annealing time is 1 hour~3 hours, which may include, but is not limited to, 1 hour, 1.5 hours, 2 hours, 2.5 hours, and 3 hours. Annealing can eliminate the internal stress generated during grinding and promote the homogenization of element diffusion; if the temperature is too low or the time is too short, the stress will not be sufficiently eliminated, and if the temperature is too high or the time is too long, it may lead to grain coarsening.
[0057] Specifically, spark plasma sintering includes: loading annealed mixed powder into a graphite mold and placing it in a spark plasma sintering furnace; first, evacuating or filling with an inert gas to form a protective atmosphere; then, applying sintering pressure along the axial direction; simultaneously, applying a pulsed direct current to the graphite mold and the mixed powder; utilizing the coupling effect of the discharge plasma generated between the powder particles by the pulsed current, Joule heating, and axial pressure to rapidly raise the temperature to the sintering temperature and hold it at that temperature; after holding, releasing the pressure, cooling with the furnace, and demolding to obtain a dense alloy billet. The protective atmosphere is a vacuum or an inert gas, such as argon.
[0058] The sintering temperature is 950℃~1050℃, which may be, but is not limited to, 950℃, 980℃, 1000℃, 1020℃ or 1050℃; the sintering pressure is 30MPa~50MPa, which may be, but is not limited to, 30MPa, 35MPa, 40MPa, 45MPa or 50MPa; the holding time is 5 minutes to 15 minutes, which may be, but is not limited to, 5 minutes, 8 minutes, 10 minutes, 12 minutes or 15 minutes.
[0059] The pulsed DC current uses a 12:2 on / off pulse mode, meaning that after every 12 pulses on, 2 pulses are off; the pulse width is 3.0ms to 3.6ms, but can be, but is not limited to, 3.0ms, 3.1ms, 3.2ms, 3.3ms, 3.4ms, 3.5ms, or 3.6ms; the pulse group frequency, based on a complete cycle of one on / off pulse, is 20Hz to 25Hz, but can be, but is not limited to, 20Hz, 21Hz, 22Hz, 23Hz, 24Hz, or 25Hz; the pulse current duty cycle is 85% to 90%, but can be, but is not limited to, 85%, 86%, 87%, 88%, or 89%. Or 90%; calculated by dividing the effective current displayed by the equipment by the effective cross-sectional area of the sintered blank, the apparent pulse current density is 300A / cm²~800A / cm², which may be, but is not limited to, 300A / cm², 400A / cm², 500A / cm², 600A / cm², 700A / cm² or 800A / cm².
[0060] For example, by applying an axial pressure of 40 MPa under vacuum conditions, using a 12:2 on / off pulse mode, controlling the single pulse width to be 3.3 ms, the pulse group frequency to be approximately 21.6 Hz, the duty cycle to be approximately 85.7%, and the apparent pulse current density to be 500 A / cm², and heating to 1000℃ and holding for 10 minutes, an alloy billet with fine grains, uniform structure, and high density can be obtained.
[0061] Spark plasma sintering (SPCS) utilizes the synergistic effects of pulsed current discharge activation, Joule heating, and axial pressure. It features rapid heating, short holding time, high density, and the ability to inhibit grain growth, which is beneficial for preserving the fine-grained structure obtained from mechanical alloying and improving the interfacial bonding between Cu-Cr and the reinforcing metal phases. However, if the sintering temperature, pressure, current density, or holding time is too low, the discharge activation, diffusion, and rearrangement of powder particles are insufficient, resulting in inadequate densification and high porosity, leading to a decrease in hardness, conductivity, and compressive strength. Conversely, if the sintering temperature, pressure, current density, or holding time is too high, grain coarsening, localized overheating, and even melting and loss of low-melting-point phases and copper phases can easily occur, resulting in uneven microstructure and component segregation, thus degrading material properties. The single-pulse width, pulse group frequency, and duty cycle jointly determine the discharge energy and heating rhythm within a single cycle and should be matched with the aforementioned temperature and pressure to ensure uniform heating and a stable and controllable densification process.
[0062] This application also provides an electrical contact material, including the alloy material described above.
[0063] The electrical contact material of this application is based on the excellent properties of the aforementioned alloy material, and has advantages such as high hardness, good conductivity, strong resistance to arc erosion, and low current-cutting value, which can meet the stringent requirements of medium and high voltage vacuum switchgear for contact materials.
[0064] This application also provides a switching device, including the electrical contact material as described above.
[0065] Specifically, the switchgear includes high-voltage vacuum switches, circuit breakers, or contactors. The electrical contact material of this application, when applied to the aforementioned switchgear, can significantly improve the breaking capacity and service life of the switch, while reducing maintenance costs.
[0066] The following are specific embodiments. They are intended to provide a more detailed description of this application to help those skilled in the art and researchers better understand it. The technical conditions described do not constitute any limitation on this application. Any modifications made within the scope of the claims of this application are protected by the claims.
[0067] Unless otherwise stated, all raw materials and reagents used in the following examples are commercially available or can be prepared by known methods. Experimental methods not specifying particular conditions in the examples were performed under conventional conditions, such as those described in literature, books, or methods recommended by the manufacturer.
[0068] Performance testing methods
[0069] The material prepared in this application embodiment was subjected to performance testing as follows: the density of the contact was measured using a density meter based on Archimedes' principle. The conductivity of the contact was measured using an eddy current conductivity meter. The hardness of the sample was measured using a Vickers hardness tester at room temperature, with a load of 100 g and a loading time of 3 s. The contact alloy before and after arc erosion was weighed using an electronic balance, and its mass change was calculated.
[0070] Example 1
[0071] This embodiment provides an alloy material (CuCr38Ni2), the preparation method of which is as follows:
[0072] (1) Take Cu powder, Cr powder and Ni powder with a purity of 99.9% and an average particle size of 325 mesh, and weigh them according to the mass ratio of Cu:Cr:Ni = 60:38:2.
[0073] (2) The mixed powder was placed in a high-energy ball mill with a ball-to-material ratio of 15:1. Anhydrous ethanol was added as a process control agent and the mixture was ball-milled at 900 r / min for 13 hours.
[0074] (3) Anneal the ball-milled powder at 650°C under argon protection for 2 hours.
[0075] (4) The annealed powder is loaded into a graphite mold, and under vacuum conditions, an axial pressure of 40 MPa is applied in a discharge plasma sintering furnace and a pulsed DC current is applied. The pulsed DC current adopts a 12:2 on / off pulse mode, the single pulse width is 3.3 ms, the pulse group frequency is about 21.6 Hz, the duty cycle is about 85.7%, and the apparent pulse current density is 500 A / cm². After heating to 1000℃, it is held for 10 minutes.
[0076] Performance characterization: Hardness is 251 HV, electrical conductivity is 8.6% IACS. The surface exhibits a honeycomb-like appearance after arc ablation, with minimal droplet splashing.
[0077] Example 2
[0078] This embodiment provides an alloy material (CuCr32.5Bi7.5), the preparation method of which differs from that of Example 1 in that: in step (1), the powder mass ratio is Cu:Cr:Bi = 60:32.5:7.5.
[0079] Performance characteristics: Hardness is 170 HV, conductivity is 12.0% IACS. Withstand voltage is 7.19×10³ kV / m, and current cutoff drops to 3.8A.
[0080] Example 3
[0081] This embodiment provides an alloy material (CuCr38Fe2), the preparation method of which differs from that of Example 1 in that: in step (1), the powder mass ratio is Cu:Cr:Fe = 60:38:2.
[0082] Performance characterization: Hardness is 308 HV, electrical conductivity is 18.5% IACS. The arc-ablated surface is smooth and free of cracks.
[0083] Example 4
[0084] This embodiment provides a composite alloy material (CuCr38Ni1Fe1) with added reinforcing metals. Its preparation method is basically the same as in Example 1, except that in step (1), the mass ratio of Cu powder, Cr powder, Ni powder, and Fe powder is:
[0085] Cu∶Cr∶Ni∶Fe=60∶38∶1∶1.
[0086] The above-mentioned mixed powder was placed in a high-energy ball mill at a ball-to-powder ratio of 15:1, and anhydrous ethanol was added as a process control agent. The mixture was ball-milled at 900 r / min for 13 hours. Subsequently, it was annealed at 650℃ for 2 hours under argon protection. Finally, the annealed mixed powder was loaded into a graphite mold and subjected to spark plasma sintering at 1000℃ and 40 MPa for 10 minutes to obtain CuCr38Ni1Fe1 alloy material.
[0087] Microstructural characterization results showed that Ni and Fe were relatively uniformly distributed in the copper matrix and around the chromium phase, without obvious refining metal segregation. The combined addition of Ni and Fe improved the Cu-Cr phase interface bonding and promoted the refinement of the powder and chromium phase microstructure, resulting in alloy materials with high hardness and good resistance to arc erosion. After arc ablation, the material surface was relatively smooth, with no obvious cracks observed and minimal droplet splashing.
[0088] Comparative Example 1
[0089] This comparative example provides an alloy material (CuCr40), the preparation method of which differs from that of Example 1 in that: in step (1), the powder mass ratio is Cu:Cr = 60:40, and no third element is added.
[0090] Performance characterization: Hardness 223 HV, electrical conductivity 25.5% IACS. The arc-ablated surface is uneven with a large number of droplets splashed out.
[0091] Comparative Example 2
[0092] This comparative example provides an alloy material (CuCr30Ni10) with a Ni content exceeding the limits specified in this application. Its preparation method is basically the same as in Example 1, except that in step (1), the mass ratio of Cu powder, Cr powder, and Ni powder is:
[0093] Cu∶Cr∶Ni=60∶30∶10.
[0094] The alloy material prepared in this comparative example has a hardness of 198 HV, an electrical conductivity of 7.3% IACS, a compressive strength of 6.18×10³ kV / m, and a current cutoff of 4.7 A.
[0095] Microstructural observations revealed that increasing the Ni content to 10% resulted in significant Ni-enriched regions and decreased uniformity of chromium phase distribution in the alloy. After arc ablation, large localized craters and droplet splashing appeared on the material surface. Compared to the CuCr38Ni2 alloy of Example 1, the hardness, electrical conductivity, and compressive strength of this comparative example decreased, while the current-cutting value increased, indicating that excessively high Ni content is detrimental to improving the overall performance of the alloy.
[0096] Comparative Example 3
[0097] This comparative example provides an alloy material (CuCr25Bi15) with a Cr content lower than the limit specified in this application and a Bi content higher than the limit specified in this application. Its preparation method is basically the same as that of Example 1, except that in step (1), the mass ratio of Cu powder, Cr powder, and Bi powder is:
[0098] Cu∶Cr∶Bi=60∶25∶15.
[0099] The alloy material prepared in this comparative example has a hardness of 132 HV, an electrical conductivity of 8.7% IACS, a compressive strength of 5.62×10³ kV / m, and a current cutoff of 5.2 A.
[0100] Microstructural observations revealed that, due to the reduction of the Cr content to 25%, the chromium phase in the alloy struggled to form a uniform and continuous dispersed structure; simultaneously, excess Bi agglomerated in localized areas. Following arc ablation, significant ablation pits, cracks, and droplet splashing appeared on the material surface. Compared to the CuCr32.5Bi7.5 alloy of Example 2, the hardness, electrical conductivity, and compressive strength of this comparative example were significantly reduced, while the current-carrying capacity increased, indicating that the overall material performance declined significantly when the Cr and Bi contents exceeded the limits specified in this application.
[0101] Performance Comparison Analysis
[0102] The key performance data of the above embodiments and comparative examples are summarized in Table 1 below.
[0103] Table 1
[0104]
[0105] This application is as follows Figure 1 The images shown are SEM images and particle size distribution diagrams of the alloy materials from Examples 1, 2, and Comparative Example 1 of this application. Figure 2 The images shown are SEM images and EDS results of the alloy materials of Examples 1, 2, and Comparative Example 1 of this application. By adding trace amounts of nickel, iron, or bismuth to the CuCr40 alloy, the microstructure of the alloy was optimized by utilizing the synergistic effect of the reinforcing metal with chromium and copper, resulting in a comprehensive balance between hardness, pressure resistance, and flow cutoff performance. Compared with CuCr40 of Comparative Example 1, the hardness of Example 1 (containing nickel) increased by 12.6%, and the flow cutoff value decreased by 12.2%; the pressure resistance of Example 2 (containing bismuth) increased by 7.1%; and the hardness of Example 3 (containing iron) increased by 38.1%, the pressure resistance increased by 18.5%, and the flow cutoff value decreased by 12.2%.
[0106] In the alloy materials provided in this application, by selecting different types of reinforcing metals (nickel, iron, bismuth), the final properties of the materials can be directionally controlled to meet the needs of different application scenarios. Adding nickel significantly improves the material's hardness primarily through solid solution strengthening, while simultaneously increasing the viscosity of the arc pool to suppress droplet splashing, resulting in a smoother and more uniform ablation morphology. Adding bismuth significantly improves the material's voltage withstand strength and reduces the current cutoff value. Simultaneously, by forming a protective oxide film and reconstructing the chromium phase distribution, it effectively disperses arc energy and extends arc life. Adding iron significantly refines the powder and greatly improves the material's hardness through solid solution strengthening. Furthermore, iron accelerates arc diffusion and movement by increasing thermal conductivity and its ferromagnetism, resulting in an extremely smooth ablation surface and excellent resistance to localized deep ablation. This application employs a preparation process combining mechanical alloying and spark plasma sintering. High-energy ball milling ensures thorough mixing and mechanical alloying of the various metal elements, followed by spark plasma sintering to achieve densification, resulting in alloy materials with fine grains and uniform microstructure.
[0107] The electrical contact material of this application includes the aforementioned alloy material, which has excellent comprehensive performance and is superior to traditional CuCr40 electrical contact material in terms of hardness, resistance to arc erosion, and current-cutting value.
[0108] The switchgear of this application uses the aforementioned electrical contact material, which is suitable for medium and high voltage vacuum switches and can improve the breaking capacity and service life of the switchgear.
[0109] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0110] The above embodiments merely illustrate several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.
Claims
1. An alloy material, characterized in that, The composition comprises, by weight percentage, 59% to 61% copper, 32% to 38% chromium, and 1% to 7.5% reinforcing metal, said reinforcing metal including one or more of nickel, iron, and bismuth.
2. The alloy material as described in claim 1, characterized in that, The sum of the mass percentages of the reinforcing metal and chromium is 39% to 41% of the alloy material.
3. The alloy material as described in claim 1 or 2, characterized in that, The average grain size of the alloy material is 10 μm to 50 μm.
4. A method for preparing an alloy material, characterized in that, Includes the following steps: Prepare metallic copper, metallic chromium, and reinforcing metallic elements according to the composition of the alloy material according to any one of claims 1 to 3; The mixture of the copper, chromium and reinforcing metals is then ground, annealed and subjected to spark plasma sintering.
5. The method for preparing the alloy material as described in claim 4, characterized in that, The grinding conditions must meet one or more of the following conditions: (1) Rotation speed is 850 r / min~950 r / min; (2) The grinding media includes anhydrous ethanol; (3) The ball-to-material ratio is (14~16):1; (4) The grinding time is 10 to 15 hours.
6. The method for preparing the alloy material as described in claim 4, characterized in that, Annealing requires one or both of the following conditions to be met: (1) The annealing temperature is 600℃~700℃; (2) The annealing time is 1 to 3 hours.
7. The method for preparing the alloy material according to any one of claims 4 to 6, characterized in that, The conditions for spark plasma sintering must satisfy one or more of the following conditions: (1) The sintering temperature is 950℃~1050℃; (2) The sintering pressure is 30 MPa ~ 50 MPa; (3) The heat preservation time is 5 to 15 minutes; (4) The discharge plasma sintering is performed using a pulsed DC current with a 12:2 on / off pulse mode.
8. An electrical contact material, characterized in that, Includes the alloy material as described in any one of claims 1 to 3.
9. A switching device, characterized in that, Includes the electrical contact material as described in claim 8.
10. The switching device as claimed in claim 9, characterized in that, The switching equipment includes high-voltage vacuum switches, circuit breakers, or contactors.